The Friendshipâ€™s Values in Teenlit Dealova, Rahasia Bintang and Tetralogy â€œKosan Sodaâ€ by Dyan Nuranindya (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The novel by Dyan Nuranindya namely Dealova, Rahasia Bintang and Tetralogy "Kosan Soda," namely Canting Cantiq, Cinderella Rambut Pink, Rock N Roll Onthel and Kotak Pelangi. Teenlit by Dyan Nuranindya explains that experiences with friends have an important role in the lives of teenagers. In Teenlit, it is illustrated that every teenager has a friend who always supports positive things from the main character so that the main character can reach his goals. The study aimed to describe the values â€‹â€‹of friendship in teenlit by Dyan Nuranindya. The method used in this study is descriptive analysis and dialectical, which is also part of the approach to the theory of tetralogy structuralism. The results of this study are the value of friendship in teenlit Dyan Nuranindya, which includes trust, empathy, honesty, confidentiality, and togetherness. The value of friendship can be used as a reference in assessing the value of friendship in teenlit by Dyan Nuranindya. This research is useful to add to the wealth of research and develop related knowledge in the field of literature, especially the relation with teenlit.